2017
DOI: 10.5395/rde.2017.42.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Discoloration of various CAD/CAM blocks after immersion in coffee

Abstract: ObjectivesThis study evaluated color differences (ΔEs) and translucency parameter changes (ΔTPs) of various computer-aided design/computer-aided manufacturing (CAD/CAM) blocks after immersion in coffee.Materials and MethodsEight CAD/CAM blocks and four restorative composite resins were evaluated. The CIE L*a*b* values of 2.0 mm thick disk-shaped specimens were measured using the spectrophotometer on white and black backgrounds (n = 6). The ΔEs and ΔTPs of one day, one week, and one month immersion in coffee or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 33 publications
(42 reference statements)
8
56
1
2
Order By: Relevance
“…Fitting of CAD/CAM dentures were superior to conventional dentures, resulting in enhanced retention and lower traumatic ulcer‐frequency with CAD/CAM dentures . Composition, properties, and preparation requirement can be found in Table …”
Section: Subtractive Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations
“…Fitting of CAD/CAM dentures were superior to conventional dentures, resulting in enhanced retention and lower traumatic ulcer‐frequency with CAD/CAM dentures . Composition, properties, and preparation requirement can be found in Table …”
Section: Subtractive Manufacturingmentioning
confidence: 99%
“…Composition of CAD/CAM silicate ceramics, properties, and preparation requirement can be found in Table …”
Section: Subtractive Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials are conventional and used in direct and indirect restorative procedures . In a digital dentistry era, the possibility of performing in‐office restorations, through computer‐aided design and computer‐aided manufacturing (CAD/CAM) systems, has increased the demand and the use of polymer‐based prefabricated blocks for using in CAD/CAM systems . Such a material emerged as an excellent alternative for the fabrication of interim prostheses since it is polymerized industrially under standard conditions of temperature and pressure, which results in better chemical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have shown that different resins present similar Δ E values . Some studies have shown a superior behavior of composites for CAD/CAM . In the meantime, no study compared or evaluated the Δ E of composites for CAD/CAM systems in comparison to the composites of conventional laboratory processing in acidic/staining solutions in short and long periods of immersion.…”
Section: Introductionmentioning
confidence: 99%